Enhancing the benefits of value chain development: Addressing gender disparities in Kenyan and Ugandan common bean value chains - Wilkus, Erin Lynn; Francesconi, Gian N. (International Center for Tropical Agriculture, 2017)
This study contributed to a better understanding of current gender disparities that can help to ensure future inclusive market development and associated benefits. The analysis is based on empirical evidence from female and male small and medium enterprise (SME) owners along the common bean value chain that served urban and peri-urban bean markets in Kenya and Uganda. The value chain was evaluated based on cross-sectional data collected from 349 interconnected small and medium enterprises (SMEs). SMEs spanned three value chain levels, namely traders and wholesalers, which were dominated by male proprietors, and shopkeepers, which were dominated by female-proprietors